Measurement of Patient-Derived Glioblastoma Cell Response to Temozolomide Using Fluorescence Lifetime Imaging of NAD(P)H - Diana V. Yuzhakova; Daria A. Sachkova; Marina V. Shirmanova; Artem M. Mozherov; Anna V. Izosimova; Anna S. Zolotova; Konstantin S. Yashin (Pharmaceuticals, 2023)
Personalized strategies in glioblastoma treatment are highly necessary. One of the possible approaches is drug screening using patient-derived tumor cells. However, this requires reliable methods for assessment of the response of tumor cells to treatment. Fluorescence lifetime imaging microscopy (FLIM) is a promising instrument to detect early cellular response to chemotherapy using the autofluorescence of metabolic cofactors. Here, we explored FLIM of NAD(P)H to evaluate the sensitivity of patient-derived glioma cells to temozolomide (TMZ) in vitro. Our results demonstrate that the more-responsive cell cultures displayed the longest mean fluorescence lifetime τm after TMZ treatment due to an increase in the protein-bound NAD(P)H fraction α2 associated with a shift to oxidative phosphorylation. The cell cultures that responded poorly to TMZ had generally shorter τm, i.e., were more glycolytic, and showed no or insignificant changes after treatment. The FLIM data correlate well with standard measurements of cellular drug response—cell viability and proliferation index and clinical response in patients. Therefore, FLIM of NAD(P)H provides a highly sensitive, label-free assay of treatment response directly on patient-derived glioblastoma cells and can become an innovative platform for individual drug screening for patients.